Інформаційна технологія розробки інтернет-магазину ігрової техніки - Пронін, І. В. (ХНУРЕ, 2023)
The functionality of the online store of gaming equipment includes many features that allow users to enjoy the convenience and speed of purchasing the goods they are interested in. In particular, the functionality includes: convenient search for products, filters and categories, the ability to track the status of an order and communicate with the seller; convenient payment and delivery methods that will satisfy the requirements of any client; the possibility of obtaining discounts and promotions that will be available to both new and regular customers. All these functionalities create the conditions for a comfortable and safe purchase of gaming equipment in the online store.